Sistem Informasi Manajemen Pengarsipan Surat Masuk Dan Surat Keluar (Studi Kasus : Ma Darul Ihya Bogor) - Mahmudah, Sintia; Widiastuti, Lisda; Ernawati, Siti (STMIK Budi Darma, 2019)
At MA Darul Ihya Bogor correspondence is an important means of communication. One of the problems in managing letters at the MA Darul Ihya Bogor is the inefficient filing of mail data that still uses a manual system. With the number of incoming letters and outgoing letters each meeting makes a letter that is in the archive so that the search becomes inefficient because not all files are arranged properly. One effort to overcome this problem is to create an in and outgoing mail management information system. The research method used in this study is the method of Lifecycle Development (SDLC) with the Waterfall model. The waterfall model (waterfall) is often also called a linear sequential (linear sequential) model. The results of this study are to make this site-based management information system can facilitate business administration in the process of inputting incoming and outgoing mail data, searching for incoming and outgoing mail data, making reports of incoming and outgoing mail data producing the required information quickly and accurately.